INFLUENCE OF MAGNETIC STORMS ON THE CONDITION OF PATIENTS WITH ARTERIAL HYPERTENSION - Kamalova Sayorakhon Salokhiddin kizi (Web of Journals Publishing, 2025)
Magnetic storms caused by solar activity are a significant environmental factor that can affect human health, especially in patients with arterial hypertension. This review examines current understanding of the pathophysiological mechanisms of geomagnetic activity impact on the cardiovascular system. It summarizes the results of large epidemiological and clinical studies confirming the relationship between magnetic storms and deterioration of hypertensive patients’ health, including increased blood pressure, more frequent complaints, and increased hospitalizations. Particular attention is paid to meteosensitivity as a predisposing factor. Practical recommendations for prevention and adaptation of therapy during periods of geomagnetic instability are also provided. The data obtained emphasize the importance of taking into account the geophysical environment in clinical practice and the need for further scientific research in this area.
Keywords: Magnetic storms, arterial hypertension, meteosensitivity, geomagnetic activity, cardiovascular diseases, prevention, pressure.